A feasibility study on Fresh N' Dips - Capumpue, Lovie Mae; Del Rosario, Henry Jr; Lee, Ma. Glaiza; Manuel, Catherine Marie
FRESH N' DIPS is the brand name of the new product venture to be endorsed by Um Pue Deleeman Partnerships (UPDP) that provides better fresh food choices with a balance of economy and quality, it offers an all-natural fresh fruits and vegetables snack served with dips. This also features the customers' freedom of choice and convenience. A market Study was conducted to see if there is an existing demand for the type of product idea. The market segmentation revealed that target market includes students, young professionals, and people with busy lifestyles and on-the go within the age range of 15-39 years old and with a minimum annual income of Php 100,000. The target location was determined to be a mall within Quezon City (QC). Marketing costs incurred is estimated to be 3% of annual revenue or around PhP 68,500 for the first year of operations. A technical Study was performed and showed that the supply of raw materials was abundant; the capacity plan was proven to be effective; and because of the effective inventory management, a production schedule for the fifth year was found to be twice of the first year. Was found to be twice of the first year. The target retail outlet among the malls in QC is SM North EDSA. The project would incur cost of around PhP 10,000,000 for five years; and was proven to be environmentally feasible. An Organization and Management Study was done to determine the type of ownership of the company- a partnership. Also shown are the organizational structure, duties and responsibilities of each worker, work schedule and salaries expense and benefits incurred. Fresh N' Dips would employ a General Manager and three outlet staff. A Soci-Profitability Study was conducted to see if the project has positive effects on the people, society and economic, it was shown that the product showcased nutritional value (raw material wise). Moreover, the employment of workers contributed to the country's economy. Furthermore, the cost-benefit ratio was computed to be less than 1.0 which implied that benefit overweighed costs. A financial Study was conducted to estimate the project's cost and sources of financing. At the end of the fifty year of operations, a net profit of PhP 1,654,571.61 would be generated. The venture is profitable with a payback period of one year and three months. As an overall conclusion, Fresh N' Dips is a feasible business idea.